A Study of Postictal Complications and Co-Morbidities of Status Epilepticus in Emergency Department of Tertiary Hospital of Bundelkhand Region, Central India (GAIMS Journal of Medical Sciences, 2024)
Introduction: The postictal state is a temporary condition that occurs after seizures, often characterized by EEG slowing or suppression, and can last from minutes to days. Seizures can be accompanied by various postictal complications, including headache, automatism, delirium, psychosis, functional deficits, neuropsychological deficits, and abnormal behavioral manifestations. Effective management of postictal states requires identification of associated comorbidities and underlying neurological and systemic disorders. However, there is limited information regarding the causes, prevalence, and optimal treatment of postictal complications following status epilepticus. This study aimed to determine the different types of postictal complications and comorbidities.Materials and Methods: Patients with status epilepticus were observed after their seizure episode subsided, and their medical history and comorbidities were recorded. It was a cross sectional observation study. 100 participants were selected for the study at MLB Medical College, Jhansi, between March 2020 and November 2021. Written informed consent was obtained from allparticipants after explaining the study's objectives and procedures.Results: The most common postictal complication observed in our study was headache, experienced by 51% of patients after the seizure subsided. Delirium was observed in approximately 28% of patients, while psychosis and automatism were reported by 9% and 8% of patients, respectively.Conclusions: The results of our study indicate that individuals with seizures have significantly higher odds of experiencing various comorbid conditions compared to those without seizures. The strongest association was found between seizures and stroke.